5-hydroxymethyl-cytosine enrichment of non-committed cells is not a universal feature of vertebrate development - Almeida, Rimple D.; Loose, Matthew; Sottile, Virginie; Matsa, Elena; Denning, Chris; Young, Lorraine; Johnson, Andrew D.; Gering, Martin; Ruzov, Alexey (Landes Bioscience, 2012)
5-hydroxymethyl-cytosine (5-hmc) is a cytosine modification that is relatively abundant in mammalian pre-implantation embryos and embryonic stem cells (Esc) derived from mammalian blastocysts. Recent observations imply that both 5-hmc and Tet1/2/3 proteins, catalyzing the conversion of 5-methyl-cytosine to 5-hmc, may play an important role in self renewal and differentiation of Escs. here we assessed the distribution of 5-hmc in zebrafish and chick embryos and found that, unlike in mammals, 5-hmc is immunochemically undetectable in these systems before the onset of organogenesis. In addition, Tet1/2/3 transcripts are either low or undetectable at corresponding stages of zebrafish development. however, 5-hmc is enriched in later zebrafish and chick embryos and exhibits tissue-specific distribution in adult zebrafish. Our findings show that 5-hmc enrichment of non-committed cells is not a universal feature of vertebrate development and give insights both into evolution of embryonic pluripotency and the potential role of 5-hmc in its regulation.